2020
DOI: 10.1038/s41467-020-18591-6
|View full text |Cite
|
Sign up to set email alerts
|

Trait phenomenological control predicts experience of mirror synaesthesia and the rubber hand illusion

Abstract: In hypnotic responding, expectancies arising from imaginative suggestion drive striking experiential changes (e.g., hallucinations) — which are experienced as involuntary — according to a normally distributed and stable trait ability (hypnotisability). Such experiences can be triggered by implicit suggestion and occur outside the hypnotic context. In large sample studies (of 156, 404 and 353 participants), we report substantial relationships between hypnotisability and experimental measures of experiential cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
259
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(282 citation statements)
references
References 85 publications
(106 reference statements)
20
259
3
Order By: Relevance
“…It is worth sounding a note of caution about interpreting evidence for (especially) altered experiences of embodiment in terms of Bayesian inference on bodyrelated sensory signals. For example, a recent study by Lush and colleagues has revealed a link between subjective reports of illusory ownership in the well-known 'rubber hand illusion' (RHI) and hypnotic suggestion (Lush et al, 2020). In this study, individual differences in the strength of the RHI correlated tightly with individual differences in hypnotic suggestibility (which the authors refer to as trait 'phenomenological control').…”
Section: Predictive and Explanatory Power Of Pp As A Systematic Basismentioning
confidence: 54%
“…It is worth sounding a note of caution about interpreting evidence for (especially) altered experiences of embodiment in terms of Bayesian inference on bodyrelated sensory signals. For example, a recent study by Lush and colleagues has revealed a link between subjective reports of illusory ownership in the well-known 'rubber hand illusion' (RHI) and hypnotic suggestion (Lush et al, 2020). In this study, individual differences in the strength of the RHI correlated tightly with individual differences in hypnotic suggestibility (which the authors refer to as trait 'phenomenological control').…”
Section: Predictive and Explanatory Power Of Pp As A Systematic Basismentioning
confidence: 54%
“…This would suggest that referral of touch is not a necessary condition for developing a sense of ownership in the RHI, but rather any combination of at least two sensory modalities (e.g., vision and proprioception). Another possibility is that these responses reflect some level of participant suggestibility (Marotta et al, 2016), which have been found to predict some variance (<10%) in participant questionnaire responses across conditions and statement types in the RHI (Lush et al, 2020). Of course, this claim is based on the assumption that referral of touch is a necessary condition for ownership in the RHI, which may be unfounded.…”
Section: Discussionmentioning
confidence: 99%
“…Both wear time and functional use (the two components comprising our daily use score) were found to correlate with perceived prosthesis embodiment (rho (42) = 0.46, p = 0.002, rho (42) = 0.48, p < 0.001, respectively). However, self-report questionnaire-based measures of embodiment are arguably crude and prone to bias and inter-individual differences (e.g., in suggestibility; Lush et al, 2020 ). We therefore turned to a more implicit measure of embodiment—spontaneously produced communicative hand gestures with the prosthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, one-handers who gesture more with their prosthesis, and produced more symmetrical gesture patterns, were also shown to report more positive feelings of prosthesis embodiment and greater prosthesis use in everyday life. As gesticulation was spontaneously generated by the participants, and was never explicitly mentioned as part of the task, it is resistant to recent criticisms relating to inherent biases in the induction of embodiment measures, such as the rubber hand illusion ( Lush, 2020 ; Lush et al, 2020 ). Our findings thus provide a novel means for implicitly indexing embodiment in artificial limbs, with relevance for how artificial limbs are being operated in real-world contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation